Attrition and reactivation of a childhood language: the case of returnee heritage speakers - Flores, Cristina (2020)
This paper discusses the dynamic nature of childhood bilingualism by analyzing oral speech from returnee heritage speakers (HSs) of Portuguese, who grew up in Germany, but moved to Portugal in childhood/adolescence. The first set of data from 14 speakers show that the length of exposure to German predicts the rate of (in)accurate production of nominal inflection, indicating that the speakers’ morphological knowledge has not been sufficiently stabilized due to the return. The second dataset from one returnee HS who was re-immersed in the German environment after a four-year stay in Portugal. The comparative analysis of the speaker’s performance 13 months after moving away from Germany and 11 months after being re-exposed to German reveals a significant decrease of inaccurate case, gender and plural marking, which supports the hypothesis of re-stabilization of linguistic knowledge. Overall, the findings emphasize the effects of lack of exposure on the development of HSs’ bilingual competence.